Integrating Internationalization to Reframe Nursing Education: Its Challenges, Opportunities and Implications in The Pandemic Era - Acob, Joel Rey (Al-Hijrah Indonesia, 2024)
Internationalization as a concept determines individual institution’s initiative to be visible in the arena of academic pursuits. The health crisis confronted by the world had highlighted the role of educational societies to strive amidst complications for global connectivity. Linkages at the moment become vital as nursing leaders design platform which is resilient to the test and demands of time. Challenging the quality of nursing education post-pandemic poses threat to delivery of safe nursing practice if higher education institution failed to safeguard its implementation through updating policies regarding compulsory and programmatic accreditation. This perspective documents various initiatives as opportunities to enhance if not sustain quality nursing education and attracting foreign students while keeping adherence to mantra of excellence instruction, research and training through borderless approach.